Relevance of Implementing a Neurodidactic Approach in the Educational Process - Zhalgasbaevna, Abilova Gulbakhar; Abdullayevich, Khakimov Zoxid (International Journal of Formal Education, 2025)
This article substantiates the relevance of implementing a neurodidactic approach in the educational process. The concepts of neuropedagogy, neurodidactics, and the educational process are elucidated. The fundamental principles of the neurodidactic approach are delineated, considered within the framework of the primary spheres of personality development: motivational-needs, cognitive, emotional-volitional, and individual-psychological. The author posits that the most efficacious model of the educational process is predicated precisely on the neurodidactic approach. The necessity of developing novel forms of teacher training is underscored. The article demonstrates, through the example of the neurodidactic approach, the potential for enhancing the effectiveness of the educational process by means of an individualized approach to learning, contingent upon the specific psychophysiological developmental characteristics of the child.